SEMANTIC LAYERS OF V. STEFANYK’S SKETCH «THE OLD DAYS» - Kozlov, R. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The sketch «The Old Days» is one of the few given elegiac, not tragic mood by the author. Written in hard times of sorrow for the mother, it contains autobiographical concepts summarized in the collective image of the past. Behind these images Vasyl Stefanyk represents his own understanding of cultural progress of the nation and, implicitly, the role of intelligentsia in it.